2004
DOI: 10.1117/1.1803846
|View full text |Cite
|
Sign up to set email alerts
|

Focused ion beam for microscopy and in situ sample preparation: application on a crustacean digestive system

Abstract: We prove that the focused ion beam (FIB) machine can be used as a microscope and as an in situ cutting device for tissue and cells. For the first time we obtain high-resolution ion images, complemented by electron imaging of different animal tissues both from uncoated and coated samples. In our study, we select the digestive system of Porcellio scaber (isopoda, crustacea) as a test system for FIB microscopy and in situ sample preparation. After the milling operation, some of the ultrastructural elements of hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
(20 reference statements)
1
21
0
Order By: Relevance
“…The main advantage of FIB-SEM imaging is permitting faster visualization of serial ultra-thin sections, which optimizes the adjustments needed for identification of the target structures (23,24). As a result, we confirmed that chondrocytes in the proliferative and the hypertrophic zones extend their short cytoplasmic processes to the cartilaginous fibrils that parallel the longitudinal axis of the growth plate, and that vesicular structures are present in the intercolumnar septa -even at the proliferative zone (Figs.…”
Section: Discussionsupporting
confidence: 70%
“…The main advantage of FIB-SEM imaging is permitting faster visualization of serial ultra-thin sections, which optimizes the adjustments needed for identification of the target structures (23,24). As a result, we confirmed that chondrocytes in the proliferative and the hypertrophic zones extend their short cytoplasmic processes to the cartilaginous fibrils that parallel the longitudinal axis of the growth plate, and that vesicular structures are present in the intercolumnar septa -even at the proliferative zone (Figs.…”
Section: Discussionsupporting
confidence: 70%
“…Other investigators have developed protocols to study conventionally prepared biological samples with a FIB/SEM system (Drobne et al 2004(Drobne et al , 2005aHing et al 2003;Milani et al 2004a;Moulders 2003;Young 1993). Since the FIB/SEM system allows in situ observation of ultrastructural features, we questioned whether it is possible to observe unprepared, in situ FIB milled cells by an FIB/SEM system.…”
Section: Introductionmentioning
confidence: 97%
“…The low ion beam current polishing (typically 100 to 300 pA) can be used to reduce the damaged layer (Drobne et al, 2004(Drobne et al, , 2005aIshitani et al, 1995). Otherwise, not much is known about the surface damage induced by FIB.…”
Section: Introductionmentioning
confidence: 97%
“…The FIB is widely used in semiconductor industry and material sciences, and most recently it has entered into life sciences (Ballerini et al, 1997;Drobne et al, 2004Drobne et al, , 2005aIshitani et al, 1995;Milani et al, 2006a,b).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation